Melissa: product development tuned with trends research (ModaPalavra e-periódico, 2018)
Julia Joner is a Fashion Designer who, at the moment, works as a supervisor of the Design team of shoewear brand Melissa. The interview shows the company productive processes, their creatives dynamics and how trends research is integrated into product development.
Keywords: product design; trends research; Melissa